An unusual cause of cutaneous ulceration. (2nd January 2017) - Wlodek, C.; Ng, Y.; Bovill, B.; Johnson, E. M.; Bhatt, N.; Shipley, D.
Abstract : Clickhere for the corresponding questions to this CME article.